2019
DOI: 10.3847/1538-4357/ab1b27
|View full text |Cite
|
Sign up to set email alerts
|

Ejection of Double Knots from the Radio Core of PKS 1510–089 during the Strong Gamma-Ray Flares in 2015

Abstract: PKS 1510-089 is a bright and active γ-ray source that showed strong and complex γ-ray flares in mid-2015 during which the Major Atmospheric Gamma Imaging Cherenkov telescopes detected variable very high energy (VHE; photon energies >100 GeV) emission. We present long-term multi-frequency radio, optical, and γ-ray light curves of PKS 1510-089 from 2013 to 2018, and results of an analysis of the jet kinematics and linear polarization using 43 GHz Very Long Baseline Array data observed between late 2015 and mid-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…et al. 2005;Tavecchio & Ghisellini 2008Marscher et al 2010;MacDonald et al 2015;Park et al 2019c). Also, Nakahara et al (2018) explained the observed jet radii for NGC 4261 (Nakahara et al 2018) and Cygnus A (Boccardi et al 2016b;Nakahara et al 2019) being systematically larger than those for M87 and NGC 6251 (see Figure 8 in Nakahara et al 2018) with the spinesheath scenario.…”
Section: Jet Velocity Stratificationmentioning
confidence: 99%
“…et al. 2005;Tavecchio & Ghisellini 2008Marscher et al 2010;MacDonald et al 2015;Park et al 2019c). Also, Nakahara et al (2018) explained the observed jet radii for NGC 4261 (Nakahara et al 2018) and Cygnus A (Boccardi et al 2016b;Nakahara et al 2019) being systematically larger than those for M87 and NGC 6251 (see Figure 8 in Nakahara et al 2018) with the spinesheath scenario.…”
Section: Jet Velocity Stratificationmentioning
confidence: 99%
“…The variability of the spectral index indicates variations of intricate source properties, most likely changes in the optical depth (Trippe et al 2011). Along the same lines, Park et al (2019) interpreted that when the radio spectra are optically thick an emerging component is close to the core and when the spectra become optically thin the component is well separated from the core. This interpretation describes well what happened during the FP1 and is compatible with the shock-injet model (e.g.…”
Section: Cross-correlations For the Separate Flaring Periodsmentioning
confidence: 89%
“…This model has been invoked to explain the origin of gammaray flares in PKS 1510-089 (e.g. Marscher et al 2010;Park et al 2019). Particularly, the gamma-ray flare of 2015 of this object was found to have origin at ∼10 pc from the base of the jet.…”
Section: Location Of the Emission Region And Dominant Emission Mechan...mentioning
confidence: 98%
See 1 more Smart Citation
“…We can do this by measuring the turnover frequency and the flux density, and the size of the source at the turnover frequency (Rybicki & Lightman 1986). In previous studies using the Interferometric Monitoring of GAmma-ray Bright AGNs (iMOGABA) program (Lee et al 2013(Lee et al , 2016b(Lee et al , 2017aAlgaba et al 2018a,b;Kim et al 2018;Park et al 2019) which is a part of the Korean VLBI Network (KVN) key science programs, magnetic field strengths of a few mG were found in the SSA regions of the relativistic jets in S5 0716+714 (Lee et al 2017a) and 1633+382 (Algaba et al 2018a).…”
Section: Introductionmentioning
confidence: 99%